Psychological Well-Being Remaja Akhir: Studi Peran Social Support dan Self-Efficacy - Rizkika Alhayyu; Puspa Rahayu Utami Rahman; Regi Ramadan (EduInovasi: Journal of Basic Educational Studies, 2025)
Every individual basically has a drive to achieve inner satisfaction and a balanced psychological condition, known as psychological well-being. Late adolescents tend to experience significant changes in the process of becoming adults, which often causes developmental pressure and has an impact on psychological well-being. This study aims to determine the effect of social support and self-efficacy on the psychological well-being of late adolescents in Karawang. The method in this study uses a quantitative approach with a causality design. The number of participants was 390 people aged 17 to 21 years who were selected using convenience techniques. Data collection was carried out using three measuring instruments, namely the Multidimensional Scale of Perceived Social Support (MSPSS), General Self-Efficacy Scale (GSES), and Ryff's Psychological Well-Being Scale. The results of the study showed a sig value of 0.00 (p< 0.05) namely Ha was accepted and Ho was rejected, meaning that social support and self-efficacy had a significant effect on the psychological well-being of late adolescents. The R² value of 0.777 shows that 77.7% of psychological well-being has a strong influence on variations in social support and self-efficacy. This shows that support from the social environment of family, friends, and important figures in an individual's life, as well as the individual's ability to believe in their potential in facing life's challenges, are important determining factors in helping adolescents achieve optimal psychological well-being.